Against determinism: A reassessment of Marcel Mauss’s essay on seasonal variations - Bravo, Michael (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractThe famous “Seasonal Variations of the Eskimo” by Marcel Mauss has traditionally been understood as a text about the dominance of the social world in determining and imposing seasonal organisation on the physical world. Such interpretations of seasonality typically fail to take adequate account of contemporary European and North American debates about land and society. Paying close attention to the historical context of the essay reveals strong evidence for an alternative reading: that it was written as a polemic against anthropogeographical theory from the school of Friedrich Ratzel. The prime target was Hans-Peder Steensby, an intellectual disciple of Ratzel. Depicting Steensby as exclusively concerned with physical geography, Mauss reinterpreted his evidence within his own evidential context of social morphology. He concludes that the crucial principle governing Inuit seasonal life is the symbiosis between the social and physical worlds—and not the physical determination or technological adaptations diagnosed by the anthropogeographers. Understanding that Mauss was seeking to distance his own sociology/anthropology from geography provides an opportunity to reflect on the divergence in theoretical orientation and choice of research problems amongst the community of Inuit studies.